Numerical investigation of melting of paraffin-wax phase change material in cone capsule with different alignments - Afzal, Asif; Buradi, Abdulrajak; Ağbulut, Ümit; Alwetaishi, Mamdooh; Fayaz, H.; Park, Sung Goon; Bordas, Stéphane P. A. (Elsevier, 2025)
The ability of phase change material to store thermal energy and how quickly the solid-liquid phase transition occurs depends on its thermal properties. The present numerical work focused on the melting of paraffin wax encapsulated in cone geometry using the Ansys fluent simulation tool. The cone capsule is 10 mm in size, has a base diameter, and has an axis height of 15 mm, with a vertical and horizontal orientation. The conservative mass, momentum, and energy equations are discretized and using the finite volume method are solved with a transient implicit method. The melting process of paraffin wax is captured with the help of the enthalpy-porosity equation with a mushy zone constant value of 104, while the PISO algorithm does pressure-velocity coupling. The transient temperature, mass fraction, temperature gradient per second, and mass fraction gradient per second of paraffin wax are plotted. From the results, it is observed that 100 % melting of PCM takes approximately 30 s and 36 s in the vertical and horizontal positions of the cone capsule, respectively. Further, it is also observed that the maximum drop in temperature gradient per unit of time is 19 % and 16 % in vertical and horizontal cone positions, respectively. Finally, it is concluded that the vertical cone provides improved heat transfer performance and uniform temperature distribution than the horizontal cone.